Coping with Brain Disorders using Neurotechnology - Pedro A, Valdes-Sosa (Penerbit Universiti Sains Malaysia, 2012)
Brain disorders account for more than 34% of the global burden of disease, crippling nations by decreasing their “mental capital”—with greater effect in developing countries. Early detection is the key to their management, but establishing such programmes seems nearly impossible due to the high prevalence of the dysfunctions as compared with the high cost of neuroimaging devices. Thus, at first sight, the research of the Decade of the Brain and the international Human Brain Mapping Project might seem to be condemned to benefit only a small elite. Cuba has shown that is not so by using neurotechnology for the last 3 decades to implement stratified active screening programmes for brain disorders at the population level. This experience has shown that, by the transformation of health indicators, an appropriate use of technology can be integrated with attention to the population at the primary levels of both health care and education. An essential component of neurotechnology is neuroinformatics, which—like its counterpart bioinformatics—combines databases, analysis tools, and theoretical models to craft tools for early disease diagnosis and management. Much work remains to be done and will depend critically on south—south cooperation to solve problems for countries with similar situations.